Tracing arsenic and antimony in mining-impacted environments: New insights from antimony isotopes - Colin Ferrari; Kevin B. White; Carol J. Ptacek; David W. Blowes (Chemical Geology, 2026)

Deciphering Sb Sources and Transport Processes in a Mining and Smelting-Impacted River System (Oruro, Bolivia): Insights from Sb Isotopes - Colin Ferrari; Eléonore Resongles; Rémi Freydier; Marizol Flores; Mauricio Ormachea; Gerardo Zamora Echenique; Corinne Casiot (Water, Air, & Soil Pollution, 2025)

The Multi-State Epigenetic Pacemaker enables the identification of combinations of factors that influence DNA methylation - Colin Farrell; Keshiv Tandon; Roberto Ferrari; Kalsuda Lapborisuth; Rahil Modi; Sagi Snir; Matteo Pellegrini (GeroScience, 2024)
Epigenetic clocks, DNA methylation-based predictive models of chronological age, are often utilized to study aging associated biology. Despite their widespread use, these methods do not account for other factors that also contribute to the variability of DNA methylation data. For example, many CpG sites show strong sex-specific or cell-type-specific patterns that likely impact the predictions of epigenetic age. To overcome these limitations, we developed a multidimensional extension of the Epigenetic Pacemaker, the Multi-state Epigenetic Pacemaker (MSEPM). We show that the MSEPM is capable of accurately modeling multiple methylation-associated factors simultaneously, while also providing site-specific models that describe the per site relationship between methylation and these factors. We utilized the MSEPM with a large aggregate cohort of blood methylation data to construct models of the effects of age-, sex-, and cell-type heterogeneity on DNA methylation. We found that these models capture a large faction of the variability at thousands of DNA methylation sites. Moreover, this approach allows us to identify sites that are primarily affected by aging and no other factors. An analysis of these sites reveals that those that lose methylation over time are enriched for CTCF transcription factor chip peaks, while those that gain methylation over time are associated with bivalent promoters of genes that are not expressed in blood. These observations suggest mechanisms that underlie age-associated methylation changes and suggest that age-associated increases in methylation may not have strong functional consequences on cell states. In conclusion, the MSEPM is capable of accurately modeling multiple methylation-associated factors, and the models produced can illuminate site-specific combinations of factors that affect methylation dynamics.

Multi-isotope (Pb, Sb) approach to trace metallic contaminant sources at a historical mining and metallurgical site - Floriane Guillevic; Magali Rossi; Eléonore Resongles; Rémi Freydier; Colin Ferrari; Cécile Quantin; Gaël Monvoisin; Jérôme Poulenard; Fabien Arnaud (Chemical Geology, 2024)

Antimony isotope fractionation during Sb(V) and Sb(III) adsorption on secondary Fe-minerals (schwertmannite, ferrihydrite) typical of mine waters - Colin Ferrari; Eléonore Resongles; Rémi Freydier; Corinne Casiot (Applied Geochemistry, 2024)

Antimony isotopic fractionation during Sb(III) oxidation to Sb(V): Biotic and abiotic processes - Colin Ferrari; Eléonore Resongles; Marina Héry; Angélique Désoeuvre; Rémi Freydier; Sophie Delpoux; Odile Bruneel; Corinne Casiot (Chemical Geology, 2023)

Drones as tools for monitoring beach topography changes in the Ligurian Sea (NW Mediterranean) - Elisa Casella; Alessio Rovere; Andrea Pedroncini; Colin P. Stark; Marco Casella; Marco Ferrari; Marco Firpo (Geo-Marine Letters, 2016)